Protective coating, positive plate and battery

By using polymer-based protective coatings and conductive particles on lithium batteries, combined with infrared spectral characteristic peaks in specific wavelength ranges, the problem of volume energy density reduction caused by the thickness of lithium battery protective coating is solved, and both safety and lightness are achieved .

CN119286312APending Publication Date: 2025-01-10ZHUHAI COSMX BATTERY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411374047.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing lithium battery protective coating is thicker, resulting in a reduced volume energy density, which makes it impossible to take into account both safety performance and lightness.

Method used

Using polymer-based protective coatings, its in-situ diffuse infrared spectrum has characteristic peaks in a specific wavelength range, including polystyrene and polybutadiene groups, combining conductive particles and additives to form a thin and flexible protective film , ensure the safety of the battery in case of mechanical abuse.

Benefits of technology

It realizes that while ensuring the safety performance of the battery, significantly reduces the thickness of the protective coating, improves the volume energy density, and enhances the safety performance of the battery's mechanical abuse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286312A_ABST
    Figure CN119286312A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a protective coating, a positive plate comprising the protective coating and a battery. The protective coating comprises a polymer, and in an in-situ diffuse reflection infrared spectrum of the protective coating, a strong peak I exists in a wave band of 696cm <-1 >-701cm <-1 >, a strong peak II exists in a wave band of 963cm <-1 >-968cm <-1 >, and a five-crack peak exists in a wave band of 2800cm <-1 >-3200cm <-1 >. The in-situ diffuse reflection infrared spectrum of the protective coating provided by the invention has a characteristic peak in a specific wave band, which indicates that the protective coating comprises a specific group and can effectively protect the battery while the thickness is relatively thin, so that the battery does not catch fire or explode under the condition of mechanical abuse.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a protective coating, a positive electrode sheet comprising the protective coating, and a battery. Background Art

[0002] The use of lithium batteries is becoming more and more popular and has penetrated into thousands of households. Therefore, the safety of batteries is of vital importance to every consumer. As electrical appliances continue to evolve and their volumes continue to shrink, batteries need to be smaller and smaller, and have higher and higher energy. In order to ensure the safety performance of lithium batteries, the industry generally adopts the method of setting a protective coating on the surface of the current collector. However, in order to ensure the safety performance of the battery, the thickness of the protective coating is relatively thick, which will inevitably increase the volume of the battery. This is inconsistent with the market's ultimate pursuit of energy density. Therefore, a safe and thin protective coating is crucial to the development of battery technology. Summary of the invention

[0003] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art, and provide a protective coating, a positive electrode sheet including the protective coating, and a battery including the protective coating and / or the positive electrode sheet. The in-situ diffuse reflection infrared spectrum of the protective coating of the present invention has a characteristic peak in a specific wavelength range, and the protective coating with the characteristic peak can effectively protect the battery while being significantly thinner than other safety measures in the industry (ensuring that the battery has a higher volume energy density), so that the battery will not catch fire or explode under mechanical abuse.

[0004] In the related art, there is a problem that the volume energy density is reduced in order to ensure the safety performance of the battery. The present invention proposes a component that can be used for a protective coating. Different from the protective coating components used in the related art, the in-situ diffuse reflectance infrared spectrum of the protective coating of the present invention has a characteristic peak in a specific wavelength range, indicating that it contains special component groups. The protective coating component enables it to effectively reduce the thickness of the coating film while ensuring the safety performance of the battery, so that the battery maintains a higher volume energy density.

[0005] The first aspect of the present invention provides a protective coating, wherein the protective coating comprises a polymer, and in an in-situ diffuse reflectance infrared spectrum of the protective coating, at 696 cm -1 -701cm -1 There is a strong peak at 963cm -1 -968cm -1 There is a strong peak 2 in the band, and it is at 2800cm -1 -3200cm -1 There are five peaks in the band.

[0006] A second aspect of the present invention provides a positive electrode sheet, which includes the protective coating described in the first aspect of the present invention.

[0007] A third aspect of the present invention provides a battery, the battery comprising the protective coating described in the first aspect of the present invention and / or the positive electrode sheet described in the second aspect of the present invention.

[0008] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0009] (1) The protective coating of the present invention can be completed in an existing industrial production line and can achieve a thinner film thickness;

[0010] (2) The battery of the present invention can take into account both volume energy density and mechanical abuse safety performance.

[0011] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 Shown is an in-situ diffuse reflectance infrared spectrum of a protective coating in an example of the present invention.

[0013] Figure 2 Shown is a scanning electron microscope (SEM) image of a protective coating in an example of the present invention.

[0014] Figure 3 FIG. 1 is a schematic diagram showing the difference in thickness between the first portion and the second portion of the protective coating in an example of the present invention, wherein: Figure 3 (a) is a top view, Figure 3 (b) is a side view.

[0015] Figure 4 Shown is a schematic structural diagram of a positive electrode sheet in an example of the present invention.

[0016] Figure 5 The figure shows a schematic diagram of the structure of the positive electrode sheet in an example of the present invention, wherein Figure 5 (a) The protective coating is provided on the positive electrode current collector side, Figure 5 In (b), the protective coating is provided on both sides of the positive electrode current collector.

[0017] Figure 6 The above is a schematic diagram of the structure of the positive electrode sheet in an example of the present invention; wherein, Figure 6 (a) The protective coating is provided on the positive electrode current collector side, Figure 6 In (b), the protective coating is provided on both sides of the positive electrode current collector.

[0018] Figure 7 It is a schematic diagram showing the dimensions of the overlapping area of ​​the orthographic projection of the protective coating on the positive electrode current collector and the orthographic projection of the positive electrode active material layer on the positive electrode current collector along the winding direction in one example of the present invention.

[0019] Figure 8 The above is a schematic diagram of the structure of the positive electrode sheet in an example of the present invention; wherein, Figure 8 (a) The protective coating and adhesive tape are provided on one side of the positive electrode current collector. Figure 8 In (b), the protective coating and adhesive tape are provided on both sides of the positive electrode current collector.

[0020] Fig. 9 FIG. 1 is a schematic diagram of the structure of a positive electrode sheet in an embodiment of the present invention; wherein, Fig. 9 (a) The protective coating and adhesive tape are provided on one side of the positive electrode current collector. Fig. 9 In (b), the protective coating and adhesive tape are provided on both sides of the positive electrode current collector.

[0021] Fig.10 FIG. 1 is a schematic diagram of the structure of a positive electrode sheet in an embodiment of the present invention; wherein, Fig.10 (a) The protective coating and adhesive tape are provided on one side of the positive electrode current collector. Fig.10 In (b), the protective coating and adhesive tape are provided on both sides of the positive electrode current collector.

[0022] Fig.11 Shown is a schematic structural diagram of a positive electrode sheet in an example of the present invention.

[0023] Fig.12 Shown is a schematic structural diagram of a battery in an example of the present invention.

[0024] Fig.13 Shown is an in-situ diffuse reflectance infrared spectrum of the protective coating obtained by disassembling a battery in an example of the present invention. DETAILED DESCRIPTION

[0025] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0026] The first aspect of the present invention provides a protective coating, wherein the protective coating comprises a polymer, and in an in-situ diffuse reflectance infrared spectrum of the protective coating, at 696 cm -1 -701cm -1 There is a strong peak at 963cm -1 -968cm -1 There is a strong peak 2 in the band, and it is at 2800cm -1 -3200cm -1There are five split peaks in the band. Figure 1 The figure shows the in-situ diffuse reflectance infrared spectrum of the protective coating in one embodiment of the present invention. It can be seen from the figure that the protective coating has a high -1 -701cm -1 Band (699cm -1 ) There is a strong peak at 963cm -1 -968cm -1 Band (966cm -1 ) has a strong peak 2, and at 2800cm -1 -3200cm -1 There are five peaks in the band (the wavelengths are 2846cm from small to large). -1 、2917cm -1 、3004cm -1 、3025cm -1 and 3069cm -1 ).

[0027] The inventors found that the in-situ diffuse reflectance infrared spectrum of the protective coating has a characteristic peak in a specific band, indicating that the protective coating contains a component with a specific group. The protective coating formed by coating with a slurry containing the component has a thin thickness and good flexibility after film formation, and can be effectively coated on the surface of the positive electrode current collector and / or the positive electrode active material layer, thereby effectively protecting the battery.

[0028] In situ diffuse reflectance infrared spectra of protective coatings at 2800 cm -1 -3200cm -1 The five-split peaks in the band indicate that the protective coating contains benzene ring groups. On this basis, the -1 -701cm -1 The presence of characteristic peaks in the band indicates the presence of polystyrene and / or its derivatives in the protective coating. The in-situ diffuse reflectance infrared spectrum of the protective coating is at 963 cm -1 -968cm -1 The presence of characteristic peaks in the band indicates that the protective coating composition contains polybutadiene and / or its derivatives.

[0029] In one example, in the five-split peak, located at 2910 cm -1 -2930cm -1 The peak intensity of the characteristic peak of the band is the largest.

[0030] In one embodiment, in the in-situ diffuse reflectance infrared spectrum of the protective coating, at 1710 cm -1 -1740cm -1 There are characteristic peaks in the band. Figure 1 As shown, from Figure 1It can be seen that the protective coating is at 1710cm -1 -1740cm -1 Band (1720cm -1 ) has a characteristic peak, which is relatively broad, that is, the protective coating has a peak at 1710cm -1 -1740cm -1 There is a broad characteristic peak in the band.

[0031] In situ diffuse reflectance infrared spectra of protective coatings at 1710 cm -1 -1740cm -1 The presence of characteristic peaks in the band indicates that the protective coating has absorbed water during the preparation and / or storage process. Since the moisture was not removed by baking before testing, water molecules formed a bond with the substances in the protective coating, causing the protective coating to absorb water at 1710 cm -1 -1740cm -1 The band has characteristic peaks.

[0032] In one embodiment, in the in-situ diffuse reflectance infrared spectrum of the protective coating, at 1450 cm -1 -1455cm -1 There is a characteristic peak in the band. In the in-situ diffuse reflectance infrared spectrum of the protective coating, at 1063cm -1 -1068cm -1 There are characteristic peaks in the band. Figure 1 It can be seen that the protective coating is at 1450cm -1 -1455cm -1 Band (1452cm -1 ) has a characteristic peak. At 1063cm -1 -1068cm -1 Band (1064cm -1 ) has characteristic peaks.

[0033] In the present invention, the in-situ diffuse reflectance infrared spectrum of the protective coating can be obtained by testing using conventional methods in the art, for example, taking at least 1 cm 2 The protective coating is used as the test sample (without physical or chemical treatment such as heat radiation drying, vacuum dehumidification, etc.) and tested in an environment with a temperature of 25°C ± 5°C and a humidity of <75% using an in-situ diffuse reflectance infrared spectrometer in an open test environment; or, the battery is disassembled to obtain the positive electrode sheet (or other components including the protective coating), and the surface coated with the protective coating is taken as the test sample (the area of ​​the safety coating is ensured to be at least 1cm 2, and the test samples are not subjected to physical or chemical treatments to remove moisture, such as heat radiation drying and vacuum dehumidification), and the test samples are tested in an environment with a temperature of 25℃±5℃ and a humidity of <75%, using an in-situ diffuse reflectance infrared spectrometer in an open test environment.

[0034] In the present invention, the monomers forming the polymer may include Wherein, R1, R2, R3, R4, R5, R6 and R7 can each independently include at least one of H, carboxyl, ester, amide, anhydride, halogen atom, ether, aldehyde, ketone, hydroxyl, substituent substituted or unsubstituted alkyl and olefin. The substituent can include at least one of carboxyl, ester, amide, anhydride, halogen atom, ether, aldehyde, ketone, hydroxyl and olefin. The anhydride can include maleic anhydride.

[0035] In the present invention, the protective coating may further include conductive particles. The conductive particles may include at least one of conductive carbon black (e.g., Carbon Black or Super P), graphene, graphene oxide, Ketjen black, carbon nanotubes, and hard carbon. The carbon nanotubes may include single-walled carbon nanotubes and / or multi-walled carbon nanotubes.

[0036] In one example, the conductive particles may further include at least one of the following materials coated with carbon, the materials may include metal particles, alloy particles, metal oxides and silicon oxides. The metal oxide may include at least one of a non-transition metal element oxide and a transition metal element oxide.

[0037] In the present invention, the substituent may be a partial substitution.

[0038] In one example, the monomers forming the polymer include styrene and butadiene.

[0039] When the battery is damaged by mechanical abuse, the positive current collector will produce metal burrs or debris that pierce the diaphragm, or because the positive active material layer is displaced and falls off, the positive current collector is exposed, so that the positive current collector is in direct contact with the negative active material layer, resulting in a strong short circuit, generating a large amount of heat in a short time, and causing the battery to catch fire and explode. The protective coating of the present invention has good flexibility and strong adhesion to the positive current collector / positive active material layer. When the battery is mechanically abused, even a thin protective coating can better protect the positive current collector, prevent debris or burrs from directly contacting the negative active material, and prevent the occurrence of short circuits. And the reason why a relatively thin protective coating can be formed is that: first, the viscosity of the slurry forming the protective coating is relatively high, and it can be achieved by leveling the surface of the positive current collector to form a coating at a relatively low solid content. The protective coating formed after the coating is dried is relatively thin. Second, the protective coating also includes conductive particles, which play a role in shearing the polymer chains in the slurry, improving the overall dispersibility, so that the protective coating slurry has a suitable viscosity; and can deepen the color of the basically colorless polymer slurry, making it easier for the entire industrial preparation process to better identify the coating appearance and coating size of the protective coating.

[0040] In the present invention, based on the total mass of the protective coating, the content of the polymer can be 80%-99.9% (for example, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.5% or 99.9%), and the content of the conductive particles can be 0.1%-20% (for example, 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5% or 0.1%).

[0041] In one example, based on the total mass of the protective coating, the content of the polymer is 98%-99.5%, and the content of the conductive particles is 0.5%-2%.

[0042] When the content of conductive particles in the protective coating is within a specific range, it can not only improve the mechanical recognition of the protective coating during the coating process, so that appearance defects can be quickly identified, which is beneficial to improving production efficiency; and because the appropriate amount of conductive particles can make the viscosity of the protective coating slurry appropriate and have a good shearing effect on the polymer chains in the protective coating slurry, it can also form a protective film with thin thickness, good flexibility and complete appearance, thereby reducing the volume of the battery and increasing the volume energy density while ensuring the safety performance of the battery.

[0043] In the present invention, the protective coating may further include additives. The additives are used to improve the coating appearance and / or slurry viscosity. Based on the total mass of the protective coating, the content of the additive may be 0.1%-20% (for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%). The additive may include at least one of polyamide (PA), polyacrylic acid (PAA), sodium polyacrylate (PAA-Na), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR).

[0044] In the present invention, based on the total mass of the protective coating, the content of the polymer can be 85%-99.8% (for example, 85%, 88%, 92%, 96%, 99% or 99.8%), the content of the conductive particles can be 0.1%-5% (for example, 5%, 3%, 2%, 1%, 0.5% or 0.1%), and the content of the additive can be 0.1%-10% (for example, 10%, 9%, 6%, 3%, 0.5% or 0.1%).

[0045] In one example, based on the total mass of the protective coating, the content of the polymer is 93%-96.5%, the content of the conductive particles is 0.5%-2%, and the content of the additive is 3%-5%.

[0046] In the present invention, the protective coating comprises a first portion and a second portion which are alternately distributed in sequence. Figure 2 The figure shows a scanning electron microscope (SEM) image of the protective coating in an example of the present invention. It can be seen from the figure that the protective coating surface presents a first part and a second part with alternating light and dark colors. The difference between the thickness of the first part and the thickness of the second part is 0.3μm-3μm, for example, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.5μm, 2μm, 2.5μm or 3μm. Figure 3 FIG. 1 is a schematic diagram showing the difference in thickness between the first portion and the second portion of the protective coating in an example of the present invention, wherein: Figure 3 (a) is a top view, Figure 3 (b) is a side view. It can be seen from the figure that the protective coating 1 includes a first portion 11 and a second portion 12 which are alternately distributed in sequence, and the difference between the thickness of the first portion 11 and the thickness of the second portion 12 is d.

[0047] In one example, a difference between the thickness of the first portion and the thickness of the second portion is 0.5 μm-1 μm.

[0048] When the protective coating is disposed on the outermost layer of the battery cell, it will be in direct contact with the battery shell (e.g., aluminum-plastic film). If the protective coating has a first portion and a second portion that are alternately distributed in sequence, and the difference in thickness between the two portions is within a specific range, the friction between the protective coating and the battery shell can be increased, the position of the battery cell in the shell can be stabilized, and the drop safety performance of the battery can be improved.

[0049] By controlling the coating method of the protective coating slurry, the first part and the second part of the protective coating are regulated to be distributed alternately in sequence. Taking advantage of the particularity of gravure roller coating, during the self-leveling process of the protective coating slurry on the surface of the positive electrode current collector, the part with pits on the gravure roller carries more slurry, and these parts will spontaneously level around. Due to the high viscosity of the slurry and the control of the time of being placed in the oven for drying, the protective coating does not have time to level to a uniform height, thus presenting the first part and the second part with alternating distribution in sequence (that is, the protective coating has alternating deep and shallow lines). The thickness difference between the first part and the second part can be regulated by adjusting the depth of the pits of the gravure roller, the solid content of the slurry, etc.

[0050] In the present invention, the thickness of the first portion may be 0.4 μm-10 μm, for example, 0.4 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0051] In one example, the thickness of the first portion is 0.8 μm-3 μm.

[0052] In one example, the thickness of the first portion is 1.1 μm-2.5 μm.

[0053] In the present invention, the thickness of the second portion may be 0.1 μm-7 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm or 7 μm.

[0054] In one example, the thickness of the second portion is 0.3 μm-2 μm.

[0055] In one example, the thickness of the second portion is 0.6 μm-1.8 μm.

[0056] In the present invention, the thickness of the first part and the thickness of the second part can be tested by conventional methods in the art, for example, by observing the cross-section of the protective coating by SEM, selecting at least 10 first parts and 10 second parts, measuring the thickness of the highest point of each first part, taking the average value, and obtaining the thickness of the first part; measuring the thickness of the lowest point of each second part, taking the average value, and obtaining the thickness of the second part.

[0057] A second aspect of the present invention provides a positive electrode sheet, which may include the protective coating described in the first aspect of the present invention.

[0058] Since the direct contact between the positive electrode current collector and the negative electrode active material layer is the most important short-circuit mode that causes battery fire, providing a protective coating on the area where the positive electrode current collector is directly exposed can effectively reduce the occurrence of battery fire, thereby improving the mechanical abuse safety performance of the battery.

[0059] In the present invention, the positive electrode sheet further comprises a positive electrode current collector and a positive electrode active material layer. Any one side surface of the positive electrode current collector may have the protective coating and / or the positive electrode active material layer.

[0060] In one example, the protective coating is located at the leading end and / or the trailing end of the positive electrode current collector along the winding direction.

[0061] In one example, one side surface of the positive electrode current collector includes the protective coating, and the other side surface of the positive electrode current collector includes the positive electrode active material layer. Figure 4 The figure shows a schematic diagram of the structure of a positive electrode sheet in an example of the present invention. It can be seen from the figure that the positive electrode sheet includes a protective coating 1, a positive electrode current collector 2 and a positive electrode active material layer 3; one side surface of the positive electrode current collector 1 includes the positive electrode active material layer 3; the other side surface of the positive electrode current collector 1 includes the protective coating 1.

[0062] In one example, along the winding direction of the positive electrode current collector, the edge of the protective coating contacts the edge of the adjacent positive electrode active material layer, and the orthographic projection of the protective coating on the positive electrode current collector does not overlap with the orthographic projection of the positive electrode active material layer on the positive electrode current collector. Figure 5 The figure shows a schematic diagram of the structure of the positive electrode sheet in an example of the present invention, wherein Figure 5 (a) The protective coating is provided on the positive electrode current collector side, Figure 5 In (b), the protective coating is provided on both sides of the positive electrode current collector. As can be seen from the figure, the positive electrode sheet includes a protective coating 1, a positive electrode current collector 2 and a positive electrode active material layer 3; Figure 5In (a), along the winding direction of the positive electrode current collector 2, on one side of the positive electrode current collector 2, the edge of the protective coating 1 contacts the edge of the adjacent positive electrode active material layer 3, and the orthographic projection of the protective coating 1 on the positive electrode current collector 2 does not overlap with the orthographic projection of the positive electrode active material layer 3 on the positive electrode current collector 2; the other side of the positive electrode current collector 2 has the positive electrode active material layer 3. Figure 5 In (b), along the winding direction of the positive electrode current collector 2, on the two side surfaces of the positive electrode current collector 2, the edge of the protective coating 1 contacts the edge of the adjacent positive electrode active material layer 3, and the orthographic projection of the protective coating 1 on the positive electrode current collector 2 does not overlap with the orthographic projection of the positive electrode active material layer 3 on the positive electrode current collector 2.

[0063] Figure 5 The protective coating is located at the tail end of the positive electrode current collector along the winding direction. Similarly, the protective coating can also be located at the head end of the positive electrode current collector along the winding direction.

[0064] The inventors of the present invention have found that providing a protective coating on the area of ​​the positive electrode current collector that is not covered by the positive electrode active material layer can effectively improve the mechanical abuse safety performance of the battery.

[0065] In one example, along the winding direction of the positive electrode current collector, at least a portion of the protective coating covers the positive electrode active material layer, and the orthographic projection of the protective coating on the positive electrode current collector partially overlaps with the orthographic projection of the positive electrode active material layer on the positive electrode current collector. Figure 6 The above is a schematic diagram of the structure of the positive electrode sheet in an example of the present invention; wherein, Figure 6 (a) The protective coating is provided on the positive electrode current collector side, Figure 6 In (b), the protective coating is provided on both sides of the positive electrode current collector. As can be seen from the figure, the positive electrode sheet includes a protective coating 1, a positive electrode current collector 2 and a positive electrode active material layer 3; Figure 6 In (a), along the winding direction of the positive electrode current collector 2, on one side of the positive electrode current collector 2, part of the protective coating 1 covers the positive electrode active material layer 3, and the orthographic projection of the protective coating 1 on the positive electrode current collector 2 partially overlaps with the orthographic projection of the positive electrode active material layer 3 on the positive electrode current collector 2; the other side of the positive electrode current collector 2 has a positive electrode active material layer 3. Figure 6 In (b), along the winding direction of the positive electrode current collector 2, on the surfaces of both sides of the positive electrode current collector 2, part of the protective coating 1 covers the positive electrode active material layer 3, and the orthographic projection of the protective coating 1 on the positive electrode current collector 2 partially overlaps with the orthographic projection of the positive electrode active material layer 3 on the positive electrode current collector 2.

[0066] Figure 6 The protective coating is located at the tail end of the positive electrode current collector along the winding direction. Similarly, the protective coating can also be located at the head end of the positive electrode current collector along the winding direction.

[0067] In the present invention, the size of the overlapping area of ​​the orthographic projection of the protective coating on the positive current collector and the orthographic projection of the positive active material layer on the positive current collector in the winding direction is 1mm-20mm, for example, 1mm, 2mm, 3mm, 4mm, 5mm, 6mm, 7mm, 8mm, 9mm, 10mm, 11mm, 12mm, 13mm, 14mm, 15mm, 16mm, 17mm, 18mm, 19mm or 20mm. Figure 7 The figure shows a schematic diagram of the dimensions of the overlapping area of ​​the orthographic projection of the protective coating on the positive electrode current collector and the orthographic projection of the positive electrode active material layer on the positive electrode current collector in an example of the present invention along the winding direction, and "L" in the figure is this dimension.

[0068] The inventor of the present invention has found that when the overlapping area of ​​the positive projection of the protective coating on the positive current collector and the positive active material layer on the positive current collector is within a specific range of size along the winding direction, it can also effectively reduce the occurrence of lithium precipitation. The reason may be that the portion of the battery pole piece (positive electrode sheet or negative electrode sheet) close to the winding tail generally has a thickness thinning area (that is, within a certain size range, the thickness of the positive electrode active material layer / negative electrode active material layer close to the winding tail is less than the thickness of the positive electrode active material layer / negative electrode active material layer away from the winding tail), and this part of the area is thinned in thickness, so the tightness of the contact and bonding between the diaphragm changes, resulting in the poor conduction ability of lithium ions. During the battery cycle, it will become a weak position where lithium precipitation occurs first. Therefore, the negative electrode sheet corresponding to this position is prone to lithium precipitation, and the protective coating of the present invention is covered in the thickness thinning area, which can act as a tape to block the release of lithium ions in the positive electrode sheet in this area, thereby preventing the occurrence of lithium precipitation in this area and extending the life of the battery.

[0069] In the present invention, the positive electrode sheet may further include adhesive tape.

[0070] In one example, along the winding direction of the positive electrode current collector, there is a spacing area between the protective coating and the positive electrode active material layer, and the adhesive tape is arranged in the spacing area; one side edge of the adhesive tape contacts the edge of the adjacent protective coating, and the other side edge of the adhesive tape contacts the edge of the adjacent positive electrode active material layer. Figure 8 The above is a schematic diagram of the structure of the positive electrode sheet in an example of the present invention; wherein, Figure 8 (a) The protective coating and adhesive tape are provided on one side of the positive electrode current collector. Figure 8 In (b), the protective coating and adhesive tape are arranged on both sides of the positive electrode current collector. As can be seen from the figure, the positive electrode sheet includes a protective coating 1, a positive electrode current collector 2, a positive electrode active material layer 3 and adhesive tape 4; Figure 8 In (a), on one side surface of the positive electrode current collector 2, along the winding direction of the positive electrode current collector 2, there is a spacing area between the protective coating 1 and the positive electrode active material layer 3, and the adhesive tape 4 is arranged in the spacing area; one side edge of the adhesive tape 4 contacts the edge of the adjacent protective coating 1, and the other side edge of the adhesive tape 4 contacts the edge of the adjacent positive electrode active material layer 3; the other side surface of the positive electrode current collector 2 includes the positive electrode active material layer 3. Figure 8 In (b), along the winding direction of the positive electrode current collector 2, there is a spacing area between the protective coating 1 and the positive electrode active material layer 3 on both side surfaces of the positive electrode current collector 2, and the adhesive tape 4 is arranged in the spacing area; one side edge of the adhesive tape 4 contacts with the edge of the adjacent protective coating 1, and the other side edge of the adhesive tape 4 contacts with the edge of the adjacent positive electrode active material layer 3.

[0071] Figure 8 The protective coating is located at the tail end of the positive electrode current collector along the winding direction, and the positive electrode active material layer is located at the head end of the positive electrode current collector along the winding direction. Similarly, the protective coating can also be located at the head end of the positive electrode current collector along the winding direction, and the positive electrode active material layer is located at the tail end of the positive electrode current collector along the winding direction.

[0072] In the present invention, the size of the adhesive tape along the winding direction can be 4mm-20mm, for example, 4mm, 5mm, 6mm, 7mm, 8mm, 9mm, 10mm, 11mm, 12mm, 13mm, 14mm, 15mm, 16mm, 17mm, 18mm, 19mm or 20mm.

[0073] In one example, a dimension of the adhesive tape along the winding direction is 5 mm-10 mm.

[0074] In one example, along the winding direction of the positive electrode current collector, there is a spacing area between the protective coating and the positive electrode active material layer, and the spacing area has the adhesive tape; at least part of the protective coating and the adhesive tape are stacked in the thickness direction, and the orthographic projection of the protective coating on the positive electrode current collector partially overlaps with the orthographic projection of the adhesive tape on the positive electrode current collector; in the overlapping area, the protective coating is close to the positive electrode current collector, and the adhesive tape is away from the positive electrode current collector.

[0075] In the present invention, the size of the overlapping area of ​​the orthographic projection of the protective coating on the positive electrode current collector and the orthographic projection of the tape on the positive electrode current collector in the winding direction can be 0.5mm-5mm, for example, 0.5mm, 1mm, 2mm, 3mm, 4mm or 5mm.

[0076] In one example, along the winding direction of the positive electrode current collector, there is a spacing area between the protective coating and the positive electrode active material layer, and the spacing area has the adhesive tape; at least part of the positive electrode active material layer and the adhesive tape are stacked in the thickness direction, and the orthographic projection of the positive electrode active material layer on the positive electrode current collector partially overlaps with the orthographic projection of the adhesive tape on the positive electrode current collector; in the overlapping area, the positive electrode active material layer is close to the positive electrode current collector, and the adhesive tape is away from the positive electrode current collector.

[0077] In the present invention, the size of the overlapping area of ​​the orthographic projection of the positive active material layer on the positive current collector and the orthographic projection of the tape on the positive current collector in the winding direction can be 0.5mm-5mm, for example, 0.5mm, 1mm, 2mm, 3mm, 4mm or 5mm.

[0078] like Fig. 9 FIG. 1 is a schematic diagram of the structure of a positive electrode sheet in an embodiment of the present invention; wherein, Fig. 9 (a) The protective coating and adhesive tape are provided on one side of the positive electrode current collector. Fig. 9 In (b), the protective coating and adhesive tape are arranged on both sides of the positive electrode current collector. As can be seen from the figure, the positive electrode sheet includes a protective coating 1, a positive electrode current collector 2, a positive electrode active material layer 3 and adhesive tape 4; Fig. 9 In (a), on one side surface of the positive electrode current collector 2, along the winding direction of the positive electrode current collector 2, there is a spacing area between the protective coating 1 and the positive electrode active material layer 3, and the spacing area has the adhesive tape 4; part of the positive electrode active material layer 3 and the adhesive tape 4 are stacked in the thickness direction, and the orthographic projection of the positive electrode active material layer 3 on the positive electrode current collector 2 partially overlaps with the orthographic projection of the adhesive tape 4 on the positive electrode current collector 2; in the overlapping area, the positive electrode active material layer 3 is close to the positive electrode current collector 2, and the adhesive tape 4 is away from the positive electrode current collector 2; and part of the protective coating 1 and the adhesive tape 4 are stacked in the thickness direction, and the orthographic projection of the protective coating 1 on the positive electrode current collector 2 partially overlaps with the orthographic projection of the adhesive tape 4 on the positive electrode current collector 2; in the overlapping area, the protective coating 1 is close to the positive electrode current collector 2, and the adhesive tape 4 is away from the positive electrode current collector 2. Fig. 9In (b), along the winding direction of the positive electrode collector 2, on both sides of the positive electrode collector 2, there is a spacing area between the protective coating 1 and the positive electrode active material layer 3, and the spacing area has the adhesive tape 4; part of the positive electrode active material layer 3 and the adhesive tape 4 are stacked in the thickness direction, and the orthographic projection of the positive electrode active material layer 3 on the positive electrode collector 2 partially overlaps with the orthographic projection of the adhesive tape 4 on the positive electrode collector 2; in the overlapping area, the positive electrode active material layer 3 is close to the positive electrode collector 2, and the adhesive tape 4 is away from the positive electrode collector 2; and part of the protective coating 1 and the adhesive tape 4 are stacked in the thickness direction, and the orthographic projection of the protective coating 1 on the positive electrode collector 2 partially overlaps with the orthographic projection of the adhesive tape 4 on the positive electrode collector 2; in the overlapping area, the protective coating 1 is close to the positive electrode collector 2, and the adhesive tape 4 is away from the positive electrode collector 2.

[0079] Fig. 9 The protective coating is located at the tail end of the positive electrode current collector along the winding direction, and the positive electrode active material layer is located at the head end of the positive electrode current collector along the winding direction. Similarly, the protective coating can also be located at the head end of the positive electrode current collector along the winding direction, and the positive electrode active material layer is located at the tail end of the positive electrode current collector along the winding direction.

[0080] Understandably, Fig. 9 Only the protective coating and the adhesive tape, and the positive electrode active material layer and the adhesive tape are stacked in the thickness direction. Both stacking the protective coating and the adhesive tape in the thickness direction or stacking the positive electrode active material layer and the adhesive tape in the thickness direction can achieve good results.

[0081] In the present invention, the size of the overlapping area of ​​the orthographic projection of the protective coating on the positive electrode current collector and the orthographic projection of the adhesive paper on the positive electrode current collector along the winding direction can be 0.5mm-5mm, for example, 0.5mm, 1mm, 2mm, 3mm, 4mm or 5mm. The size of the overlapping area of ​​the orthographic projection of the positive active material layer on the positive electrode current collector and the orthographic projection of the adhesive paper on the positive electrode current collector along the winding direction can be 0.5mm-5mm, for example, 0.5mm, 1mm, 2mm, 3mm, 4mm or 5mm.

[0082] In one example, along the winding direction of the positive electrode current collector, the edge of the protective coating is in contact with the edge of the adjacent positive electrode active material layer, and the orthographic projection of the protective coating on the positive electrode current collector does not overlap with the orthographic projection of the positive electrode active material layer on the positive electrode current collector; the adhesive tape covers part of the protective coating and part of the positive electrode active material layer. Fig.10FIG. 1 is a schematic diagram of the structure of a positive electrode sheet in an embodiment of the present invention; wherein, Fig.10 (a) The protective coating and adhesive tape are provided on one side of the positive electrode current collector. Fig.10 In (b), the protective coating and adhesive tape are arranged on both sides of the positive electrode current collector. As can be seen from the figure, the positive electrode sheet includes a protective coating 1, a positive electrode current collector 2, a positive electrode active material layer 3 and adhesive tape 4; Fig.10 In (a), along the winding direction of the positive electrode current collector 2, on one side of the positive electrode current collector 2, the edge of the protective coating 1 contacts the edge of the adjacent positive electrode active material layer 3, and the orthographic projection of the protective coating 1 on the positive electrode current collector 2 does not overlap with the orthographic projection of the positive electrode active material layer 3 on the positive electrode current collector 2; the adhesive tape 4 covers part of the protective coating 1 and part of the positive electrode active material layer 3; the other side of the positive electrode current collector 2 has a positive electrode active material layer 3. Fig.10 In (b), along the winding direction of the positive electrode current collector 2, on the two side surfaces of the positive electrode current collector 2, the edge of the protective coating 1 contacts the edge of the adjacent positive electrode active material layer 3, and the orthographic projection of the protective coating 1 on the positive electrode current collector 2 does not overlap with the orthographic projection of the positive electrode active material layer 3 on the positive electrode current collector 2; the adhesive tape 4 covers part of the protective coating 1 and part of the positive electrode active material layer 3.

[0083] Fig.10 The protective coating is located at the tail end of the positive electrode current collector along the winding direction, and the positive electrode active material layer is located at the head end of the positive electrode current collector along the winding direction. Similarly, the protective coating can also be located at the head end of the positive electrode current collector along the winding direction, and the positive electrode active material layer is located at the tail end of the positive electrode current collector along the winding direction.

[0084] The setting of adhesive tape can prevent lithium deposition in the thinned area at the end of the winding of the positive and negative electrode sheets and short circuit caused by metal burrs at the end of the winding of the negative electrode sheets. The protective coating and adhesive tape are set in the third area at the same time, which can completely cover the boundary gap between the first area where the positive electrode active material layer is located and the second area where the protective coating is located.

[0085] In the present invention, the size of the adhesive tape in the winding direction can be 4mm-20mm, for example, 4mm, 5mm, 6mm, 7mm, 8mm, 9mm, 10mm, 11mm, 12mm, 13mm, 14mm, 15mm, 16mm, 17mm, 18mm, 19mm or 20mm.

[0086] In one example, the size of the adhesive tape in the winding direction is 5 mm-10 mm.

[0087] In the present invention, the size of the adhesive paper covering the positive electrode active material layer in the winding direction may be 0.5 mm-5 mm, for example, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm or 5 mm.

[0088] In one example, along the winding direction of the positive electrode current collector, one side surface of the positive electrode current collector includes the positive electrode active material layer and the protective coating, the edge of the protective coating is in contact with the edge of the adjacent positive electrode active material layer, and the orthographic projection of the protective coating on the positive electrode current collector does not overlap with the orthographic projection of the positive electrode active material layer on the positive electrode current collector; the other side surface of the positive electrode current collector includes the positive electrode active material layer and the adhesive tape, at least part of the adhesive tape is stacked with the positive electrode active material layer in the thickness direction, and the orthographic projection of the adhesive tape on the positive electrode current collector partially overlaps with the orthographic projection of the positive electrode active material layer on the positive electrode current collector; in the overlapping area, the positive electrode active material layer is close to the positive electrode current collector, and the adhesive tape is away from the positive electrode current collector.

[0089] like Fig.11 The figure shows a schematic diagram of the structure of a positive electrode sheet in an example of the present invention. It can be seen from the figure that the positive electrode sheet includes a protective coating 1, a positive current collector 2, a positive active material layer 3 and a tape 4; along the winding direction of the positive current collector 2, one side surface of the positive current collector 2 includes the positive active material layer 3 and the protective coating 1, the edge of the protective coating 1 is in contact with the edge of the adjacent positive active material layer 3, and the orthographic projection of the protective coating 1 on the positive current collector 2 does not overlap with the orthographic projection of the positive active material layer 3 on the positive current collector 2; the other side surface of the positive current collector 2 includes the positive active material layer 3 and the tape 4, part of the tape 4 is stacked with the positive active material layer 3 in the thickness direction, and the orthographic projection of the tape 4 on the positive current collector 2 partially overlaps with the orthographic projection of the positive active material layer 3 on the positive current collector 2; in the overlapping area, the positive active material layer 3 is close to the positive current collector 2, and the tape 4 is away from the positive current collector 2. The size of the overlapping area between the orthographic projection of the adhesive tape 4 on the positive electrode current collector 2 and the orthographic projection of the positive electrode active material layer 3 on the positive electrode current collector 2 in the winding direction is D, and D can be 0.5mm-5mm, for example, 0.5mm, 1mm, 2mm, 3mm, 4mm or 5mm.

[0090] In the present invention, the positive electrode active material layer may include a positive electrode active material. The positive electrode active material may include a positive electrode active material conventionally used in the industry in the art, for example, including at least one of lithium iron phosphate, lithium cobaltate, lithium manganate, lithium titanate, lithium manganese iron phosphate, nickel cobalt manganese ternary material and nickel cobalt aluminum oxide. The positive electrode active material layer may also include a positive electrode conductor and a positive electrode binder. The positive electrode conductor may include a conductive agent conventionally used in the industry in the art, such as at least one of activated carbon, carbon nanotubes, graphene, carbon black, acetylene black, Ketjen black and carbon fiber. The graphene includes, for example, hollow graphene spheres and / or multilayer graphene. The positive electrode binder may include a binder conventionally used in the industry in the art, for example, including at least one of PVDF, SBR, CMC, polytetrafluoroethylene (PTFE), polyolefins, PA, PAA, lithium polyacrylate (PAA-Li) and PAA-Na.

[0091] In the present invention, based on the total mass of the positive electrode active material layer, the content of the positive electrode active material can be 60%-99.8% (for example, 60%, 70%, 80%, 90%, 95%, 99% or 99.8%), the content of the positive electrode conductor can be 0.1%-20% (for example, 20%, 15%, 10%, 5%, 2.5%, 0.5% or 0.1%), and the content of the positive electrode binder can be 0.1%-20% (for example, 20%, 15%, 10%, 5%, 2.5%, 0.5% or 0.1%).

[0092] In the present invention, the positive electrode active material layer may further include a positive electrode additive, for example, at least one of a dispersant, a flame retardant, a ceramic powder, a metal powder, a leveling agent, a defoaming agent, a lithium supplement agent and a filler.

[0093] In one example, based on the total mass of the positive electrode active material layer, the content of the positive electrode additive can be 0-20%, for example, 0, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.

[0094] In the present invention, the positive electrode current collector may include a metal layer and a coating located on at least one side of the metal layer. The coating may include at least one of inorganic particles, polymer materials and alloy powders. The inorganic particles include, for example, metal oxides, carbides, nitrides, metal phosphides, metal sulfides, boehmite, quartz, silicon oxides, hydrated silicon oxides, silicon, phosphorus and mineral particles. The metal oxide may include at least one of aluminum oxide, titanium oxide, magnesium oxide, zirconium oxide, antimony sulfide, barium oxide and manganese oxide. The carbide may include metal carbides and / or non-metallic carbides. The metal carbide may include at least one of titanium carbide, calcium carbide, chromium carbide, tantalum carbide, vanadium carbide, zirconium carbide and tungsten carbide. The non-metallic carbide may include boron carbide and / or silicon carbide. The nitride may include metal nitride and / or non-metallic nitride. The metal nitride may include at least one of lithium nitride, magnesium nitride, aluminum nitride, titanium nitride and tantalum nitride. The non-metallic nitride may include at least one of boron nitride, phosphorus pentane nitride and silicon tetranitride. The mineral particles may be natural or rough-processed. The polymer material may include, for example, at least one of polyolefins, polyesters, polyethers, polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), polytetrafluoroethylene (PTFE) and polyolefin acids. The thickness of the coating may be 0.1 μm-20 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm. The coating on the surface of the metal layer can improve the safety performance of the battery under mechanical abuse.

[0095] In the present invention, the adhesive tape may include at least one of acrylic acid, acrylic and rubber.

[0096] In the present invention, the thickness of the adhesive tape may be 6 μm-20 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm.

[0097] A third aspect of the present invention provides a battery, the battery comprising the protective coating described in the first aspect of the present invention and / or the positive electrode sheet described in the second aspect of the present invention.

[0098] In the present invention, the battery may include an arc region and a flat region. Fig.12The structure diagram of a battery in an example of the present invention is shown in FIG. As can be seen from the figure, the battery includes a straight area 100 and an arc area 200. The adhesive tape can be located in the arc area.

[0099] Generally speaking, the thickness of the adhesive tape is relatively thick, generally 6μm-20μm. If the winding tail position of the positive and negative electrodes of the battery is set on the straight area of ​​the battery, especially overlapping with the positive or negative electrode lugs of the battery, the thickness of the battery will increase, and the volume energy density will be lost. It will also affect the overall flatness of the battery. When the tail position is set at the edge of the straight area and the adhesive tape is set in the arc area, the volume energy density loss caused by the thickness of the battery is smaller, and the overall flatness of the battery is higher.

[0100] In the present invention, the protective coating layer may be located on a surface of the positive electrode current collector that is away from the geometric center of the battery.

[0101] In the present invention, the battery obtained through the complete preparation process is disassembled in a dry environment, and after the electrolyte is basically volatilized, the protective coating on the positive electrode sheet is subjected to in-situ diffuse reflection infrared testing. In the in-situ diffuse reflection infrared spectrum, the protective coating on the positive electrode sheet is tested at 1710 cm -1 -1740cm -1 There is no broad characteristic peak in the band. This is because the battery goes through steps such as drying, vacuuming, and electrolyte injection during the manufacturing process, and most of the water absorbed by the protective coating is removed during these processes.

[0102] In the present invention, in the in-situ diffuse reflectance infrared spectrum of the protective coating obtained after disassembling the battery, at 1790 cm -1 -1820cm -1 Has a characteristic peak. Fig.13 The figure shows the in-situ diffuse reflectance infrared spectrum of the protective coating obtained by disassembling the battery in one embodiment of the present invention. It can be seen from the figure that the protective coating has a peak at 696 cm -1 -701cm -1 Band (697cm -1 ) There is a strong peak at 963cm -1 -968cm -1 Band (965cm -1 ) There is a strong peak at 2800cm -1 -3200cm -1 There are five peaks in the band (the wavelengths are 2848cm from small to large). -1 、2922cm -1 、3007cm -1 、3028cm -1 and 3071cm -1 ), at 1790cm -1-1820cm -1 Band (1810cm -1 ) has a characteristic peak.

[0103] In the present invention, the battery may include a battery cell. The battery cell may include the positive electrode sheet. The battery cell may also include a negative electrode sheet and a separator. The battery cell may include a rolled core or a stacked core.

[0104] In one example, the battery cell includes the stacked core. The positive electrode sheet, the separator and the negative electrode sheet are stacked to obtain the stacked core (ensuring that the separator is located between the positive electrode sheet and the negative electrode sheet). The protective coating is on a side surface of the positive electrode sheet located at the outermost side of the stacked core away from the center direction of the stacked core.

[0105] In one example, the battery cell includes the winding core. The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound to obtain the winding core (ensuring that the separator is located between the positive electrode sheet and the negative electrode sheet). The protective layer is located at the winding head end and / or tail end of the winding core.

[0106] In the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector. The negative electrode active material layer may include a negative electrode active material. The negative electrode active material may include a negative electrode active material conventionally used in the industry in the field, for example, including at least one of graphite, silicon, silicon oxide, hard carbon, graphite oxide, graphene and asphalt. The negative electrode active material layer may also include a negative electrode conductive agent and a negative electrode binder. The negative electrode conductive agent may include a conductive agent conventionally used in the industry in the field, such as activated carbon, carbon nanotubes, graphene, carbon black, acetylene black, Ketjen black and carbon fiber. The graphene includes, for example, hollow graphene spheres and / or multilayer graphene. The negative electrode binder may include a binder conventionally used in the industry in the field, for example, including at least one of PVDF, SBR, CMC, polytetrafluoroethylene (PTFE), polyolefin, PA, PAA, lithium polyacrylate (PAA-Li) and PAA-Na.

[0107] In the present invention, based on the total mass of the negative electrode active material layer, the content of the negative electrode active material can be 60%-99.8% (for example, 60%, 70%, 80%, 90%, 95%, 99% or 99.8%), the content of the negative electrode conductor can be 0.1%-20% (for example, 20%, 15%, 10%, 5%, 2.5%, 0.5% or 0.1%), and the content of the negative electrode binder can be 0.1%-20% (for example, 20%, 15%, 10%, 5%, 2.5%, 0.5% or 0.1%).

[0108] In the present invention, the negative electrode active material layer may further include a negative electrode additive, for example, at least one of a dispersant, a flame retardant, a ceramic powder, a metal powder, a leveling agent, a defoaming agent and a filler.

[0109] In one example, based on the total mass of the negative electrode active material layer, the content of the negative electrode additive can be 0-20%, for example, 0, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.

[0110] In the present invention, the diaphragm includes a substrate layer. The substrate layer may include at least one of polyethylene, polypropylene and polycarbonate. The porosity of the substrate layer is greater than or equal to 10%.

[0111] In one example, the diaphragm further comprises a coating. The coating is located on at least one side surface of the substrate layer. The coating may include at least one of a binder and inorganic particles. The binder may include a binder conventionally used in the industry in the art, for example, including at least one of PVDF and PMMA. The inorganic particles may include at least one of quartz, boehmite, silicon oxide, silicon dioxide, aluminum oxide, magnesium oxide, magnesium hydroxide and aluminum hydroxide.

[0112] In the present invention, the battery may further include an electrolyte and / or an electrolyte. The electrolyte and / or the electrolyte may be a conventional choice in the industry in this field.

[0113] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.

[0114] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0115] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.

[0116] The following preparation examples are used to prepare slurries for forming the protective coating of the present invention.

[0117] Preparation Example 1

[0118] The protective coating slurry was prepared as follows:

[0119] (1) Preparation of polymer

[0120] Butadiene and styrene are mixed in a mass ratio of 19:1, and a proper amount of toluene is added to form a mixture; an initiator (butyl lithium or ammonium persulfate) is added to the mixture, and the mixture is reacted at 60° C. for 10 hours, and a polymer is obtained after cooling.

[0121] (2) The polymer prepared in step (1) and the conductive carbon black are mixed uniformly in a mass ratio of 99:1, N-methylpyrrolidone (NMP) is added, and the mixture is stirred uniformly to obtain a protective coating slurry.

[0122] Preparation Example 2

[0123] The protective coating slurry was prepared as follows:

[0124] (1) Preparation of polymer

[0125] Butadiene and styrene are mixed in a mass ratio of 1:19, and an appropriate amount of toluene is added to form a mixture; an initiator (butyl lithium or ammonium persulfate) is added to the above mixture, and the mixture is reacted at 60° C. for 10 hours, and a polymer is obtained after cooling.

[0126] (2) The polymer prepared in step (1) and the conductive carbon black are mixed uniformly in a mass ratio of 98:2, NMP is added, and the mixture is stirred uniformly to obtain a protective coating slurry.

[0127] Preparation Example 3

[0128] The protective coating slurry was prepared as follows:

[0129] (1) Preparation of polymer

[0130] Styrene and butadiene are mixed in a mass ratio of 1:1, and an appropriate amount of toluene is added to form a mixture; an initiator (butyl lithium or ammonium persulfate) is added to the mixture, and the mixture is reacted at 60° C. for 10 hours, and a polymer is obtained after cooling.

[0131] (2) The polymer prepared in step (1) and the conductive carbon black are mixed uniformly in a mass ratio of 99.5:0.5, NMP is added, and the mixture is stirred uniformly to obtain a protective coating slurry.

[0132] Preparation Example 4

[0133] This group of preparation examples is used to verify the impact of changes in "polymer".

[0134] This group of preparation examples was carried out with reference to Preparation Example 3, except that the polymer was changed, as follows:

[0135] Preparation Example 4a, the polymer is a mixture of polybutadiene and polystyrene in a mass ratio of 19:1;

[0136] Preparation Example 4b, the polymer is a mixture of polybutadiene and polystyrene in a mass ratio of 1:19;

[0137] In Preparation Example 4a, the polymer is a mixture of polybutadiene and polystyrene in a mass ratio of 1:1.

[0138] Preparation Example 5

[0139] This group of preparation examples is used to verify the effects of changes in the "mass content of polymer and conductive particles".

[0140] This group of preparation examples was carried out with reference to Preparation Example 3, except that the mass ratio of the polymer and the conductive carbon black was changed, as follows:

[0141] Preparation Example 5a, the polymer and the conductive carbon black are in a mass ratio of 80:20;

[0142] In Preparation Example 5b, the mass ratio of the polymer to the conductive carbon black is 99.9:0.1.

[0143] Preparation Example 6

[0144] This group of preparation examples is used to verify the impact of changes in "additives in the protective coating".

[0145] This group of preparation examples was carried out with reference to Preparation Example 3, except that additives were added, as follows:

[0146] In Preparation Example 6a, the polymer, conductive carbon black and polyvinylidene fluoride are uniformly mixed in a mass ratio of 95:1.5:3.5;

[0147] In preparation example 6b, the polymer, conductive carbon black and polyvinylidene fluoride are uniformly mixed in a mass ratio of 93:2:5;

[0148] In Preparation Example 6c, the polymer, conductive carbon black and polyvinylidene fluoride are uniformly mixed in a mass ratio of 96.5:0.5:3;

[0149] In Preparation Example 6d, the polymer, conductive carbon black and polyvinylidene fluoride are uniformly mixed in a mass ratio of 85:5:10;

[0150] In Preparation Example 6e, the polymer, conductive carbon black and polyvinylidene fluoride were uniformly mixed in a mass ratio of 99.8:0.1:0.1.

[0151] Preparation Example 7

[0152] Used to verify the impact of changes in "conductive particles".

[0153] The preparation was carried out in accordance with Preparation Example 3, except that the conductive particles "conductive carbon black" were replaced with multi-walled carbon nanotubes of the same mass.

[0154] Comparative Preparation Example 1

[0155] Boehmite and polyvinylidene fluoride were mixed evenly in a mass ratio of 90:10, NMP was added, and the mixture was stirred evenly to obtain a protective coating slurry.

[0156] The protective coating slurry prepared in the above preparation examples and comparative preparation examples forms a protective coating after film formation.

[0157] The following examples are provided to illustrate the batteries of the present invention.

[0158] Example 1

[0159] Prepare the battery as follows:

[0160] (1) Preparation of positive electrode sheet

[0161] Lithium cobalt oxide, polyvinylidene fluoride, conductive carbon black and multi-walled carbon nanotubes in a mass ratio of 96:2:1.5:0.5 are added to N-methylpyrrolidone (NMP) and mixed evenly to form a positive electrode slurry (solid content of 75wt%); the positive electrode slurry is evenly coated on an aluminum foil and dried;

[0162] The protective coating slurry prepared in Preparation Example 1 was Fig. 9 (b) is formed by transfer coating onto the dried aluminum foil using a gravure roller, and the thickness of the first part and the second part are controlled by adjusting the density and / or depth of the pits on the gravure roller; drying, rolling, slitting with adhesive tape (rubber, 12 μm thick), and punching to obtain a positive electrode sheet, wherein the thickness of the first part is 2 μm, the thickness of the second part is 1 μm, and the difference between the thickness of the first part and the thickness of the second part is 1 μm; the size of the adhesive tape covering the positive electrode active material layer in the winding direction is 0.5 mm, and the size of the adhesive tape covering the protective coating in the winding direction is 0.5 mm.

[0163] (2) Preparation of negative electrode sheet

[0164] Artificial graphite, styrene-butadiene rubber, sodium carboxymethyl cellulose and conductive carbon black in a mass ratio of 96.5:1:1:1.5 are added to deionized water and mixed evenly to form a negative electrode slurry (solid content is 45wt%). The negative electrode slurry is evenly coated on a copper foil, dried, rolled and die-cut to obtain a negative electrode sheet.

[0165] (3) Preparation of batteries

[0166] The positive electrode sheet prepared in step (1), the separator (8 μm thick polyethylene film) and the negative electrode sheet prepared in step (2) are wound to obtain a bare battery cell (ensuring that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role), the pole ears are welded, and the battery cell is placed in an aluminum-plastic film. The electrolyte (the organic solvent is: ethylene carbonate, propylene carbonate and propyl propionate mixed in a molar mass ratio of 1:1:1; the electrolyte salt is LiPF6, and the amount of LiPF6 added is 15% based on the total mass of the electrolyte) is injected into the dried qualified battery cell. After vacuum packaging, standing, forming, shaping, sorting and other processes, a battery is obtained, wherein the adhesive tape is located in the arc area.

[0167] Example 2

[0168] The same method is carried out as in Example 1, except that the preparation of the positive electrode sheet is as follows:

[0169] Lithium cobalt oxide, polyvinylidene fluoride, conductive carbon black and multi-walled carbon nanotubes in a mass ratio of 96:2:1.5:0.5 are added to N-methylpyrrolidone (NMP) and mixed evenly to form a positive electrode slurry (solid content of 75wt%); the positive electrode slurry is evenly coated on an aluminum foil and dried;

[0170] The protective coating slurry prepared in Preparation Example 2 was Fig. 9 (b) is formed by transfer coating onto the dried aluminum foil using a gravure roller, and the thickness of the first part and the second part are controlled by adjusting the density and / or depth of the pits on the gravure roller; drying, rolling, slitting with adhesive tape (rubber, 12 μm thick), and punching to obtain a positive electrode sheet, wherein the thickness of the first part is 1.1 μm, the thickness of the second part is 0.6 μm, and the difference between the thickness of the first part and the thickness of the second part is 0.5 μm; the size of the adhesive tape covering the positive electrode active material layer in the winding direction is 5 mm, and the size of the adhesive tape covering the protective coating part in the winding direction is 5 mm.

[0171] Example 3

[0172] The same method is carried out as in Example 1, except that the preparation of the positive electrode sheet is as follows:

[0173] Lithium cobalt oxide, polyvinylidene fluoride, conductive carbon black and multi-walled carbon nanotubes in a mass ratio of 96:2:1.5:0.5 are added to N-methylpyrrolidone (NMP) and mixed evenly to form a positive electrode slurry (solid content of 75wt%); the positive electrode slurry is evenly coated on an aluminum foil and dried;

[0174] The protective coating slurry prepared in Preparation Example 3 was Fig. 9(b) is formed by transfer coating onto the dried aluminum foil using a gravure roller, and the thickness of the first part and the second part are controlled by adjusting the density and / or depth of the pits on the gravure roller; drying, rolling, slitting with adhesive tape (rubber, 12 μm thick), and punching to obtain a positive electrode sheet, wherein the thickness of the first part is 2.5 μm, the thickness of the second part is 1.8 μm, and the difference between the thickness of the first part and the thickness of the second part is 0.7 μm; the size of the adhesive tape covering the positive electrode active material layer in the winding direction is 3 mm, and the size of the adhesive tape covering the protective coating in the winding direction is 3 mm.

[0175] Example 4 Group

[0176] Example 4a was carried out with reference to Example 1, except that the protective coating slurry prepared in Preparation Example 1 was replaced with the protective coating slurry prepared in Preparation Example 4a;

[0177] Example 4b was carried out with reference to Example 2, except that the protective coating slurry prepared in Preparation Example 2 was replaced by the protective coating slurry prepared in Preparation Example 4b;

[0178] Example 4c was carried out with reference to Example 3, except that the protective coating slurry prepared in Preparation Example 3 was replaced by the protective coating slurry prepared in Preparation Example 4c.

[0179] Example 5 Group

[0180] The method was carried out with reference to Example 3, except that the protective coating slurry prepared in Preparation Example 3 was replaced with the protective coating slurry prepared in Preparation Example 5, as follows:

[0181] Example 5a, replacing the protective coating slurry prepared in Preparation Example 3 with the protective coating slurry prepared in Preparation Example 5a;

[0182] In Example 5b, the protective coating slurry prepared in Preparation Example 3 is replaced by the protective coating slurry prepared in Preparation Example 5b.

[0183] Example 6 Group

[0184] The method was carried out with reference to Example 3, except that the protective coating slurry prepared in Preparation Example 3 was replaced with the protective coating slurry prepared in Preparation Example 6, as follows:

[0185] Example 6a, replacing the protective coating slurry prepared in Preparation Example 3 with the protective coating slurry prepared in Preparation Example 6a;

[0186] Example 6b, replacing the protective coating slurry prepared in Preparation Example 3 with the protective coating slurry prepared in Preparation Example 6b;

[0187] Example 6c, replacing the protective coating slurry prepared in Preparation Example 3 with the protective coating slurry prepared in Preparation Example 6c;

[0188] Example 6d, replacing the protective coating slurry prepared in Preparation Example 3 with the protective coating slurry prepared in Preparation Example 6d;

[0189] In Example 6e, the protective coating slurry prepared in Preparation Example 3 is replaced by the protective coating slurry prepared in Preparation Example 6e.

[0190] Example 7

[0191] The same procedure was followed as in Example 3, except that the protective coating slurry prepared in Preparation Example 3 was replaced by the protective coating slurry prepared in Preparation Example 7.

[0192] Example 8 Group

[0193] This group of embodiments is used to verify the influence of the change of "the difference between the thickness of the first part and the thickness of the second part".

[0194] This group of examples is carried out with reference to Example 3, except that the difference between the thickness of the first part and the thickness of the second part is controlled by adjusting the density and / or depth of the pits on the gravure roller, as follows:

[0195] Embodiment 8a, the thickness of the first portion is 10 μm, the thickness of the second portion is 7 μm, and the difference between the thickness of the first portion and the thickness of the second portion is 3 μm;

[0196] In Example 8b, the thickness of the first portion is 0.4 μm, the thickness of the second portion is 0.1 μm, and the difference between the thickness of the first portion and the thickness of the second portion is 0.3 μm.

[0197] Example 9

[0198] (1) Preparation of positive electrode sheet

[0199] Lithium cobalt oxide, polyvinylidene fluoride, conductive carbon black and multi-walled carbon nanotubes in a mass ratio of 96:2:1.5:0.5 are added to N-methylpyrrolidone (NMP), and mixed evenly to form a positive electrode slurry (solid content is 75wt%); the positive electrode slurry is evenly coated on both sides of the aluminum foil, dried, rolled, slit, and punched to obtain a positive electrode sheet 1;

[0200] The positive electrode slurry is uniformly coated on one side of the aluminum foil and dried; the protective coating slurry prepared in Preparation Example 3 is transfer-coated on the other side of the aluminum foil using a gravure roller; drying, rolling, slitting, and punching are performed to obtain a positive electrode sheet 2, wherein the thickness of the first part is 2.5 μm, the thickness of the second part is 1.8 μm, and the difference between the thickness of the first part and the thickness of the second part is 0.7 μm;

[0201] (2) Preparation of negative electrode sheet

[0202] Artificial graphite, styrene-butadiene rubber, sodium carboxymethyl cellulose and conductive carbon black in a mass ratio of 96.5:1:1:1.5 are added to deionized water and mixed evenly to form a negative electrode slurry (solid content is 45wt%). The negative electrode slurry is evenly coated on a copper foil, dried, rolled and die-cut to obtain a negative electrode sheet.

[0203] (3) Preparation of batteries

[0204] The positive electrode sheet 1, the positive electrode sheet 2, the separator (8 μm thick polyethylene film) prepared in step (1) and the negative electrode sheet prepared in step (2) are stacked to obtain a bare battery cell (ensuring that the separator is located between the positive electrode sheet and the negative electrode sheet to play an isolating role, the two positive electrode sheets 2 are located at the outermost sides of the bare battery cell, and the protective coating is located away from the center of the bare battery cell), the pole ears are welded, and placed in an aluminum-plastic film, and an electrolyte (the organic solvent is: ethylene carbonate, propylene carbonate and propyl propionate mixed in a molar mass ratio of 1:1:1; the electrolyte salt is LiPF6, and the amount of LiPF6 added is 15% based on the total mass of the electrolyte) is injected into the dried qualified battery cell, and a battery is obtained after vacuum packaging, standing, forming, shaping, sorting and other processes.

[0205] Example 10 Group

[0206] This group of examples is used to verify Figure 6 (b) The specific circumstances are as follows:

[0207] Embodiment 10a:

[0208] Prepare the battery as follows:

[0209] (1) Preparation of positive electrode sheet

[0210] Lithium cobalt oxide, polyvinylidene fluoride, conductive carbon black and multi-walled carbon nanotubes in a mass ratio of 96:2:1.5:0.5 are added to N-methylpyrrolidone (NMP) and mixed evenly to form a positive electrode slurry (solid content of 75wt%); the positive electrode slurry is evenly coated on an aluminum foil and dried;

[0211] The protective coating slurry prepared in Preparation Example 3 was Figure 6(b), using a gravure roller to transfer coating onto the dried aluminum foil, and controlling the thickness of the first part and the second part by adjusting the density and / or depth of the pits on the gravure roller; drying, rolling, slitting, and punching to obtain a positive electrode sheet, wherein the thickness of the first part is 2.5 μm, the thickness of the second part is 1.8 μm, and the difference between the thickness of the first part and the thickness of the second part is 0.7 μm; the size of the overlapping area of ​​the orthographic projection of the protective coating on the aluminum foil and the orthographic projection of the positive electrode active material layer on the aluminum foil in the winding direction is 1 mm.

[0212] (2) Preparation of negative electrode sheet

[0213] Artificial graphite, styrene-butadiene rubber, sodium carboxymethyl cellulose and conductive carbon black in a mass ratio of 96.5:1:1:1.5 are added to deionized water and mixed evenly to form a negative electrode slurry (solid content is 45wt%). The negative electrode slurry is evenly coated on a copper foil, dried, rolled and die-cut to obtain a negative electrode sheet.

[0214] (3) Preparation of batteries

[0215] The positive electrode sheet prepared in step (1), the separator (8 μm thick polyethylene film) and the negative electrode sheet prepared in step (2) are wound to obtain a bare battery cell (ensuring that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role), the pole ears are welded, and the battery cell is placed in an aluminum-plastic film. The electrolyte (the organic solvent is: ethylene carbonate, propylene carbonate and propyl propionate mixed in a molar mass ratio of 1:1:1; the electrolyte salt is LiPF6, and the amount of LiPF6 added is 15% based on the total mass of the electrolyte) is injected into the dried qualified battery cell, and the battery cell is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes.

[0216] Example 10b is carried out in accordance with Example 10a, except that the size of the overlapping area between the orthographic projection of the protective coating on the aluminum foil and the orthographic projection of the positive electrode active material layer on the aluminum foil in the winding direction is 10 mm.

[0217] Example 10c is carried out in accordance with Example 10a, except that the size of the overlapping area between the orthographic projection of the protective coating on the aluminum foil and the orthographic projection of the positive electrode active material layer on the aluminum foil in the winding direction is 20 mm.

[0218] Example 11 Group

[0219] This group of examples is used to verify Fig.10 (b) The specific circumstances are as follows:

[0220] Example 11a:

[0221] Prepare the battery as follows:

[0222] (1) Preparation of positive electrode sheet

[0223] Lithium cobalt oxide, polyvinylidene fluoride, conductive carbon black and multi-walled carbon nanotubes in a mass ratio of 96:2:1.5:0.5 are added to N-methylpyrrolidone (NMP) and mixed evenly to form a positive electrode slurry (solid content of 75wt%); the positive electrode slurry is evenly coated on an aluminum foil and dried;

[0224] The protective coating slurry prepared in Preparation Example 3 was Fig.10 (b), using a gravure roller to transfer coating onto the dried aluminum foil, and controlling the thickness of the first part and the second part by adjusting the density and / or depth of the pits on the gravure roller; drying, rolling, pasting with adhesive tape (rubber, thickness of 12 μm), striping, and punching to obtain a positive electrode sheet, wherein the thickness of the first part is 2.5 μm, the thickness of the second part is 1.8 μm, and the difference between the thickness of the first part and the thickness of the second part is 0.7 μm; the size of the adhesive tape in the winding direction is 5 mm, and the size of the adhesive tape covering the positive electrode active material layer in the winding direction is 0.5 mm.

[0225] (2) Preparation of negative electrode sheet

[0226] Artificial graphite, styrene-butadiene rubber, sodium carboxymethyl cellulose and conductive carbon black in a mass ratio of 96.5:1:1:1.5 are added to deionized water and mixed evenly to form a negative electrode slurry (solid content is 45wt%). The negative electrode slurry is evenly coated on a copper foil, dried, rolled and die-cut to obtain a negative electrode sheet.

[0227] (3) Preparation of batteries

[0228] The positive electrode sheet prepared in step (1), the separator (8 μm thick polyethylene film) and the negative electrode sheet prepared in step (2) are wound to obtain a bare battery cell (ensuring that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role), the pole ears are welded, and the battery cell is placed in an aluminum-plastic film. The electrolyte (the organic solvent is: ethylene carbonate, propylene carbonate and propyl propionate mixed in a molar mass ratio of 1:1:1; the electrolyte salt is LiPF6, and the amount of LiPF6 added is 15% based on the total mass of the electrolyte) is injected into the dried qualified battery cell. After vacuum packaging, standing, forming, shaping, sorting and other processes, a battery is obtained, wherein the adhesive tape is located in the arc area.

[0229] Example 11b: The same method as Example 11a is used, except that the size of the adhesive tape in the winding direction is 8 mm, and the size of the adhesive tape covering the positive electrode active material layer in the winding direction is 3 mm;

[0230] Example 11c: The same method as Example 11a is used, except that the size of the adhesive tape in the winding direction is 10 mm, and the size of the adhesive tape covering the positive electrode active material layer in the winding direction is 5 mm;

[0231] Example 11d: The same method as Example 11a is used, except that the size of the adhesive tape in the winding direction is 4 mm, and the size of the adhesive tape covering the positive electrode active material layer in the winding direction is 0.5 mm;

[0232] Example 11e: The method is carried out in accordance with Example 11a, except that the size of the adhesive tape in the winding direction is 20 mm, and the size of the adhesive tape covering the positive electrode active material layer in the winding direction is 0.5 mm.

[0233] Comparative Example 1

[0234] The same method is used as in Example 3, except that the protective coating layer is replaced by the protective coating layer slurry prepared in Comparative Preparation Example 1, wherein the formed protective coating layer does not have the first part and the second part, and the thickness of the protective coating layer is 5 μm.

[0235] Comparative Example 2

[0236] The same process is carried out as in Comparative Example 1, except that the thickness of the protective coating formed is 10 μm.

[0237] Comparative Example 3

[0238] The same procedure is carried out as in Example 3, except that the protective coating is replaced with a rubber tape (rubber, 12 μm thick) of the same length.

[0239] Comparative Example 4

[0240] The same procedure was followed as in Example 3, except that no protective coating was applied.

[0241] Test Case

[0242] (1) In-situ diffuse reflectance infrared spectroscopy test

[0243] The batteries prepared in Examples 1-11 and Comparative Example 1 were disassembled, and the surfaces coated with the protective coating were taken as test samples for testing. The results showed that: the protective coating in Examples 1-11 had a surface area of ​​696 cm -1 -701cm -1 There is a strong peak at 963cm -1 -968cm -1 There is a strong peak at 2800cm -1 -3200cm -1 There are five split peaks in the band, and at 1790cm -1 -1820cm-1 The protective coating in Comparative Example 1 does not have the above-mentioned strong peak, five-split peaks and characteristic peaks.

[0244] (2) Volume energy density test

[0245] The batteries prepared in the examples and comparative examples were tested for volume energy density, and the specific test method is as follows:

[0246] Use a battery charge and discharge tester to charge the battery to 4.25V at 0.5C constant current at 25°C, then charge it at constant voltage until the current drops to 0.02C, let it stand for 5 minutes, and then discharge it to 3V at 0.5C constant current. Record the battery's first discharge capacity Q 放 ; Use a thickness gauge to measure the battery thickness under 500PPG pressure, use an optical microscope to measure the length and width of the battery, and calculate the volume of the battery; the energy density of the battery volume = Q 放 / volume of the battery, and record the results in Table 1.

[0247] (3) Drop test

[0248] The batteries prepared in the embodiments and comparative examples were subjected to a drop test, and the specific test method is as follows: the batteries were subjected to a drop test at a height of 1.8 meters, where 1.8 meters means that the vertical distance between the starting point of the battery's drop and the drop surface is 1.8 meters; the number of drop tests was 3 rounds, totaling 18 times, and in each round, the contact point of the battery falling to the drop surface needed to be adjusted to ensure that the contact point of the battery falling to the drop surface was not repeated; the judgment criteria for the drop test were no fire, no explosion, and no leakage, that is, it was judged as passed, otherwise it was failed, and the drop test pass rate was recorded in Table 1.

[0249] (4) Acupuncture test

[0250] The batteries prepared in the examples and comparative examples were subjected to a puncture test. The specific test method was as follows: the batteries were fully charged, the test environment temperature was maintained at 25°C ± 2°C, a 4mm steel needle was used to pierce the center of the battery perpendicular to the battery plane at a speed of 0.1mm / s, and the needle was maintained for 5 minutes. If the battery did not catch fire or explode, the test was considered to have passed. The number of tests in each group was 15, and the results were recorded in Table 1.

[0251] (5) Lithium deposition test

[0252] The battery prepared in Example 10 was subjected to a lithium deposition test. The specific test method is as follows: the battery was charged to 4.2V (cutoff 2.5C) at 3C, then charged to 4.35V (cutoff 1.0C) at 2C, then charged to 4.5V (cutoff 0.2C) at 1.0C, and then left to stand for 5 minutes; then discharged to 3.0V at a rate of 0.5C, and the charge-discharge cycle was repeated 20 times; finally, it was charged to 4.2V (cutoff 2.5C) at 3C, then charged to 4.35V (cutoff 1.0C) at 2C, and then charged to 4.5V (cutoff 0.2C) at 1.0C to end. The battery was dissected in a dry room temperature environment with a humidity of less than 20%, and the surface of the negative electrode and the diaphragm corresponding to the part of the positive electrode active material layer covered by the protective coating was observed to see if there was a lithium deposition appearance, and the results were recorded in Table 1.

[0253] Table 1

[0254]

[0255]

[0256] As can be seen from Table 1, the protective coating of the present invention can ensure the safety performance of the battery while having a relatively thin thickness. Compared with the comparative example, the battery including the protective coating of the present invention can take into account high energy density, drop safety and needle puncture safety. Among them, in Example 5b, due to the small amount of conductive particles added, it is difficult to effectively identify the color appearance, and the defective rate is relatively large. In Example 11d, due to the small size of the adhesive tape in the winding direction, the adhesive tape located in the arc section is prone to curling and edging in the later stage of the battery cycle.

[0257] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A protective coating, characterized in that: The protective coating comprises a polymer. In the in-situ diffuse reflectance infrared spectrum of the protective coating, at 696 cm -1 -701cm -1 There is a strong peak at 963cm -1 -968cm -1 There is a strong peak 2 in the band, and it is at 2800cm -1 -3200cm -1 There are five peaks in the band.

2. The protective coating according to claim 1, wherein: Among the five split peaks, the one at 2910 cm -1 -2930cm -1 The peak intensity of the characteristic peak of the band is the largest; And / or, in the in-situ diffuse reflectance infrared spectrum of the protective coating, at 1710 cm -1 -1740cm -1 There are characteristic peaks in the band; and / or, in the in-situ diffuse reflectance infrared spectrum of the protective coating, at 1450cm -1 -1455cm -1 There are characteristic peaks in the band; And / or, in the in-situ diffuse reflectance infrared spectrum of the protective coating, at 1063 cm -1 -1068cm -1 There are characteristic peaks in the band.

3. The protective coating according to claim 1 or 2, wherein: The protective coating also includes conductive particles; The monomers forming the polymer include R1, R2, R3, R4, R5, R6 and R7 each independently include at least one of H, carboxyl, ester, amide, anhydride, halogen atom, ether, aldehyde, ketone, hydroxyl, substituted or unsubstituted alkyl and olefin; the substituent includes at least one of carboxyl, ester, amide, anhydride, halogen atom, ether, aldehyde, ketone, hydroxyl and olefin; Preferably, the conductive particles include at least one of conductive carbon black, graphene, graphene oxide, Ketjen black, carbon nanotubes and hard carbon; Preferably, the monomers forming the polymer include styrene and butadiene.

4. The protective coating according to claim 3, wherein: Based on the total mass of the protective coating, the content of the polymer is 80%-99.9%, and the content of the conductive particles is 0.1%-20%; preferably, based on the total mass of the protective coating, the content of the polymer is 98%-99.5%, and the content of the conductive particles is 0.5%-2%; And / or, the protective coating further comprises an additive, wherein the additive comprises at least one of polyamide, polyacrylic acid, sodium polyacrylate, polymethyl methacrylate, polyvinylidene fluoride, carboxymethyl cellulose, sodium carboxymethyl cellulose and styrene-butadiene rubber; Preferably, based on the total mass of the protective coating, the content of the polymer is 85%-99.8%, the content of the conductive particles is 0.1%-5%, and the content of the additive is 0.1%-10%.

5. The protective coating according to claim 1 or 2, wherein: The protective coating comprises a first part and a second part which are alternately distributed in sequence, and the difference between the thickness of the first part and the thickness of the second part is 0.3 μm-3 μm; preferably 0.5 μm-1 μm; And / or, the thickness of the first part is 0.4 μm-10 μm; preferably 0.8 μm-3 μm; more preferably 1.1 μm-2.5 μm; And / or, the thickness of the second portion is 0.1 μm-7 μm; preferably 0.3 μm-2 μm; more preferably 0.6 μm-1.8 μm.

6. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the protective coating according to any one of claims 1 to 5; the positive electrode sheet further comprises a positive electrode current collector and a positive electrode active material layer; any one side surface of the positive electrode current collector has the protective coating and / or the positive electrode active material layer; Preferably, the protective coating is located at the leading end and / or trailing end of the positive electrode current collector along the winding direction.

7. The positive electrode sheet according to claim 6, wherein: At least one side surface of the positive electrode current collector satisfies one of the following conditions: (a) along the winding direction of the positive electrode current collector, the edge of the protective coating layer contacts the edge of the adjacent positive electrode active material layer, and the orthographic projection of the protective coating layer on the positive electrode current collector does not overlap with the orthographic projection of the positive electrode active material layer on the positive electrode current collector; (b) Along the winding direction of the positive electrode current collector, at least a portion of the protective coating covers the positive electrode active material layer, and the orthographic projection of the protective coating on the positive electrode current collector partially overlaps with the orthographic projection of the positive electrode active material layer on the positive electrode current collector; preferably, the size of the overlapping area in the winding direction is 1mm-20mm.

8. The positive electrode sheet according to claim 6, wherein: The positive electrode sheet further includes adhesive tape, and at least one side surface of the positive electrode current collector satisfies one of the following conditions: (c) along the winding direction of the positive electrode current collector, there is a spacing region between the protective coating and the positive electrode active material layer, and the adhesive tape is arranged in the spacing region; one side edge of the adhesive tape contacts the edge of the adjacent protective coating, and the other side edge of the adhesive tape contacts the edge of the adjacent positive electrode active material layer; (d) along the winding direction of the positive electrode current collector, there is a spacing region between the protective coating and the positive electrode active material layer, and the spacing region has the adhesive tape; At least part of the protective coating is stacked with the adhesive tape in the thickness direction, and the orthographic projection of the protective coating on the positive electrode current collector partially overlaps with the orthographic projection of the adhesive tape on the positive electrode current collector; in the overlapping area, the protective coating is close to the positive electrode current collector, and the adhesive tape is away from the positive electrode current collector; preferably, the size of the overlapping area in the winding direction is 0.5mm-5mm; And / or, at least part of the positive electrode active material layer and the adhesive tape are stacked in the thickness direction, and the orthographic projection of the positive electrode active material layer on the positive electrode current collector partially overlaps with the orthographic projection of the adhesive tape on the positive electrode current collector; in the overlapping area, the positive electrode active material layer is close to the positive electrode current collector, and the adhesive tape is away from the positive electrode current collector; preferably, the size of the overlapping area in the winding direction is 0.5mm-5mm; (e) Along the winding direction of the positive electrode current collector, the edge of the protective coating is in contact with the edge of the adjacent positive electrode active material layer, and the orthographic projection of the protective coating on the positive electrode current collector does not overlap with the orthographic projection of the positive electrode active material layer on the positive electrode current collector; the adhesive tape covers part of the protective coating and part of the positive electrode active material layer; preferably, the size of the adhesive tape in the winding direction is 4mm-20mm, and the size of the adhesive tape covering the positive electrode active material layer in the winding direction is 0.5mm-5mm.

9. A battery, characterized in that: The battery comprises the protective coating according to any one of claims 1 to 5 and / or the positive electrode sheet according to any one of claims 6 to 8.

10. The battery according to claim 9, wherein The battery comprises an arc region and a straight region, and the protective coating is located on a surface of the positive electrode current collector that is away from the geometric center of the battery; And / or, the adhesive tape is located in the arc area.

Citation Information

Patent Citations

  • Battery cell pole piece and battery cell assembled from battery cell pole piece

    CN110518249A

  • Secondary battery and electric device

    CN116830346A

  • Pole piece and secondary battery

    CN220233232U